2023
DOI: 10.1182/bloodadvances.2022007719
|View full text |Cite
|
Sign up to set email alerts
|

CD11c regulates neutrophil maturation

Abstract: Neutrophils are the first-line defense immune cells against invading microbes. The bone marrow releases mature neutrophils into a circulation on a regular basis. In sepsis and other severe infections, a significant number of neutrophils is required, leading into an accelerated production of neutrophils when immature neutrophils are also released to meet a demand in these settings despite their less effective functions for microbial eradication. Here, we discovered that CD11c was expressed in neutrophils, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…We previously showed that CD11c plays a role in proliferation and apoptosis of developing neutrophils ( 3 ). Therefore, we assessed if proliferation and apoptosis was also involved in the maintenance of BM and splenic B cells in the presence or absence of CD11c.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that CD11c plays a role in proliferation and apoptosis of developing neutrophils ( 3 ). Therefore, we assessed if proliferation and apoptosis was also involved in the maintenance of BM and splenic B cells in the presence or absence of CD11c.…”
Section: Resultsmentioning
confidence: 99%
“…Bone marrow (BM) cells were obtained and cultured in 6 well plates in RPMI1640 supplemented with 10% heat inactivated FBS, glutamine, penicillin, streptomycin, GM-CSF (20 ng/mL) and IL-4 (5 ng/mL). At day 3, the culture medium was entirely discarded and replaced with freshly warmed medium containing GM-CSF and IL-4 ( 3 ). At day 7, part of cells was subjected to lipopolysaccharide (LPS) 10 µg/mL stimulation for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD11c has also been shown to play a significant role in activating immune and inflammatory responses during P. aeruginosa infections, thus contributing to the defense against the pathogen ( Metruccio et al., 2017 ). Recent research on murine subjects has demonstrated that CD11c plays a significant role in regulating the neutrophil maturation process and its associated effector functions ( Hou et al., 2023 ). In a mouse study on P. aeruginosa corneal infections, initiating apoptosis of neutrophils at an earlier stage resulted in better disease outcomes ( Zhou et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…An uncontrolled inflammatory response and endothelial barrier dysfunction characterise sepsis and ALI/ARDS 9,10 . During the progression of the disease, polymorphonuclear neutrophils (PMNs) are the first line of immune defence against pathogens 11 . In addition to their well‐known defence mechanisms, such as phagocytosis and degranulation, neutrophils can release neutrophil extracellular traps (NETs)—webs of DNA material decorated with bactericidal proteins—to efficiently ensnare microorganisms in the circulation 12 .…”
Section: Introductionmentioning
confidence: 99%